Konsep motivasi dasar dan aplikasi dalam lembaga pendidikan Islam - Ayok Ariyanto; Sulistyorini Sulistyorini (Universitas Muhammadiyah Ponorogo, 2020)
Motivation is often interpreted as a lot of things that determine the success and development of an Islamic education institution or not, certainly not the only determinant of success, but many studies say that motivation occupies a very strategic position in the process of developing educational institutions. So that through this paper will be given an overview of how the basic motivational concepts in Islamic education institutions and their applications. The much developed paradigm surrounding motivation will be the focus of the study and analysis in this paper. So from the concept of motivation that is still theoretical, the writer will describe it up to the technical level in the most basic and applicable authority in Islamic educational institutions.